A Comprehensive Intervention for Promoting Successful Aging Amongst Older People With Diabetes With Below-Normal Cognitive Function—A Feasibility Study - Natovich, Rachel; Gayus, Noa; Azmon, Michal; Michal, Hila; Gury Twito, Omri; Yair, Tomer; Raudoi, Svetlana; Kapra, Ori; Cukierman-Yaffe, Tali (Frontiers in Endocrinology, 2020)
Background: Older people with diabetes have an increased risk for disability and cognitive dysfunction, which may impede self-care capacity. These are not evaluated routinely in current health systems. In the Center for Successful Aging with Diabetes, patients over the age of 60 undergo multi-disciplinary evaluation days and are provided with an integrated (cognitive, physical, nutritional, and medical) treatment plan. Among individuals with below-normal cognitive function, self-adherence to these recommendations poses a challenge. Thus, the aim of this study was to test the feasibility of a multidisciplinary intervention amongst older people with diabetes with below-normal cognitive function and sub-optimal glucose control. Methods: Patients with a MoCA score under 26 and A1C>=7.5% participated in a two-arm intervention: A) a medical intervention: monthly meetings with a diabetes nurse-educator, supervised by a diabetes specialist and study psychologist during which changes in their pharmacological regimen of glucose, blood pressure, and lipid control were made and B) a cognitive/physical rehabilitation intervention. This arm consisted of 1) an intensive phase-group meetings which included computerized cognitive training, aerobic, balance, and strength exercise, and group discussions and 2) a monthly consolidation phase. Outcomes included change in A1C, change in strength, balance, and aerobic exercise capacity as well as change in quality of life. Results: After 12 months there was a 0.7% reduction in A1C. After 3 months there was a statistically significant improvement in physical indices, including aerobic capacity (6-minute walk), balance (FSST) and indices assessing the risk of fall (10-meter walk, time up and go). There was no additional improvement in physical indices between the 3 and 12 month visits. For some of the physical measures, the improvement observed after 3 months persisted partially to the 12-month visit. Conclusions: This feasibility study provides preliminary data that support the efficacy of the complex interventions described. The findings suggest that this older population would require an ongoing “intensive phase” intervention. Larger prospective randomized trials are needed.